What is the risk of prostate cancer mortality following negative systematic TRUS-guided biopsies? A systematic review. Issue 12 (18th December 2020) - Kawa, Sandra Miriam; Benzon Larsen, Signe; Helgstrand, John Thomas; Iversen, Peter; Brasso, Klaus; Røder, Martin Andreas
Abstract : Objective: To investigate the risk of prostate cancer-specific mortality (PCSM) following initial negative systematic transrectal ultrasound-guided (TRUS) prostate biopsies. Design: Systematic review. Data sources: PubMed and Embase were searched using a string combination with keywords/Medical Subject Headings terms and free text in the search builder. Date of search was 13 April 2020. Study selection: Studies addressing PCSM following initial negative TRUS biopsies. Randomised controlled trials and population-based studies including men with initial negative TRUS biopsies reported in English from 1990 until present were included. Data extraction: Data extraction was done using a predefined form by two authors independently and compared with confirm data; risk of bias was assessed using the Newcastle–Ottawa Scale for cohort studies when applicable. Results: Four eligible studies were identified. Outcomes were reported differently in the studies as both cumulative incidence and Kaplan-Meier estimates have been used. Regardless of the study differences, all studies reported low estimated incidence of PCSM of 1.8%–5.2% in men with negative TRUS biopsies during the following 10–20 years. Main limitation in all studies was limited follow-up. Conclusion: Only a few studies have investigated the risk of PCSM following initial negative biopsies and all studies included patients before the era of MRI of the prostate. However, the studies point to the fact that the risk of PCSM is low following initial negative TRUS biopsies, and that the level of prostate-specific antigen before biopsies holds prognostic information. This may be considered when advising patients about the need for further diagnostic evaluation. PROSPERO registration number: CRD42019134548.